Evaluation of Diagnostic Values in NCCT and MRI of the Patients With Cerebral Venous or Sinus Thrombosis in Loghman Hakim Hospital in Tehran 2014-2018 - Hatami, Hossein; Danesh, Niyousha; Shojaei, Maziar; Rabie Hamedani, Amir (International Clinical Neuroscience Journal, 2019)
Background: Cerebral venous and sinus thrombosis (CVT) is the rare type of stroke, which can be fatal or causes significant morbidity. CVT could cause by multiple etiologies and risk factors and could present with many signs and symptoms such as a headache, seizure or altered mental status. The gold standard for diagnosing CVT is magnetic resonance venography (MRV) or computed tomographic venography (CTV), as these modalities are not available in many health centers and the early diagnosis of this disease improves significantly the outcome of treatment, we evaluated the diagnostic values of CT and magnetic resonance imaging (MRI) in CVT patients. Methods: We compiled and investigated the radiological and clinical records of 92 patients with the final diagnosis of CVT; we observed the sign of thrombosis in 74 patients who had either the non-contrast CT or MRI plus MRV. We statistically analyzed the sensitivity, specificity, positive predictive value, negative predictive value, accuracy, the positive and negative likelihood ratio of these modalities. Results: Our results demonstrated that the sensitivity of CT scan is 60.5%, and its specificity is 66.7%. The positive predictive value of CT is 85%, and its negative predictive value is 34%. Our study demonstrated that the accuracy of CT in diagnosing CVT patients is 62%. Besides our results showed that the sensitivity of MRI in diagnosing CVT is 87%, and the specificity of MRI is 76.9%. Hence the positive predictive value of MRI is 94%, and the negative predictive value is 58%, and the accuracy of this modality is 85% Conclusion: In the absence of gold standard modalities, MRI and CT scan have relatively good diagnostic values, besides MRI is more beneficial between the two, moreover we found that CVT is more prevalent among women and in warm seasons.